A review on various methods of collaborative computing - Mohd Afiq Bin Zamanhuri; Zalilah Abd Aziz; Rose Hafsah Abd Rauf; Elly Johana Johan; Noratikah Shamsudin (Institute of Advanced Engineering and Science, 2019)
Currently, mosques in Malaysia distribute their lecture schedules either on paper-based form or by uploading the schedule on their social media platform. This has some disadvantages such as paper schedules are susceptible to damages and information on social media platform is often not updated to current changes. Collaborative Computing is a system that enable individuals to work together remotely by making use of the reach ability of the internet. In order to utilise the Internet’s obvious advantages over paper-based and rapid information distribution and asynchronous communication, a review is conducted to study the available methods of collaborative computing, further analyse current research papers. Result shows that Centralized Computing method is the most suitable method for developing collaborative mobile application for Islamic Lectures schedule.